Central Mucoepidermoid Carcinoma Radiographically Mimicking an Odontogenic Lesion - Lucas Novaes Teixeira; Erick Gomes Perez; Ana Cláudia Garcia Rosa; Sandro Régis Rodrigues Lima; Mariana Quirino Silveira Soares; Fabricio Passador-Santos; Vera Cavalcanti de Araújo; Andresa Borges Soares (Case Reports in Dentistry)
Central mucoepidermoid carcinoma (CMEC) is a rare pathological entity with only a few case reports in the literature. The present case reported an uncommon occurrence of CMEC mimicking an odontogenic lesion in a young patient. A 17-year-old female patient sought dental care due to a slight swelling located in the posterior region of the mandible on the left side. Radiographic exams revealed an osteolytic lesion with defined limits in relation to proximity to the pericoronal follicle of tooth #38. The clinical and radiographic diagnostic hypothesis was an odontogenic lesion. Histological sections showed the presence of a neoplasm of glandular origin, not encapsulated, with a predominantly cystic growth pattern. The neoplasm consisted of mucous, intermediate, and squamous cells. In the immunohistochemical staining, the neoplastic cells were positive for cytokeratin 7. Mucous cells were positive for PAS with diastase digestion. The final diagnosis consisted of mucoepidermoid carcinoma. The tumor was removed surgically, and the patient has shown no signs of relapse nor recurrence. In conclusion, CMEC may mimic radiographic features of various pathologies, but despite its rarity, clinicians and oral radiologists should consider CMEC as a diagnostic hypothesis for jaw lesions.